Formation of TiO2 Electrically Insulated Oxide Coatings in Mode of Alternating Current Application. Issue 46 (20th June 2016) - Karabanov, Sergey M.; Suvorov, Dmitry V.; Gololobov, Gennady P.; Stryuchkova, Yulia M.; Klyagina, Maria A.; Slivkin, Evgeniy V.
ABSTRACT: The paper presents the research results of formation peculiarities of barrier electrically insulated coatings based on titanium oxide (TiO2 ) under conditions of AC-DC electrochemical anodizing. It is shown that overlapping of AC component (at the frequency of 100 kHz – 10 MHz) leads to formation of coatings 1.2-1.4 times thicker. Dependences of the coating thickness on frequency under various ratios of the AC-component amplitude to the DC-component of anodizing voltage have been obtained.